Aesthetic and functional rehabilitation in teeth with attrition and restoration of vertical dimension due to loss of posterior occlusal support: Case report - Acosta Molina, Martha (2021)
A esthetic and functional rehabilitation is considered the maximum objective of any dental treatment, with a sustained and updated scientific base, always seeking a complete and comprehensive diagnosis, focused on presenting a treatment plan according to comprehensive needs of the patient, executed in a conscious way with an established multidisciplinary approach, with foundations based on constant dialogue between the professional, the patient and the dental technician. The objective of this report is to describe step by step the clinical stages of a multidisciplinary treatment which is based on prior diagnosis and planning; looking for the interaction of different specialties: periodontics, oral rehabilitation, aesthetic dentistry, occlusion, and an integral work with the dental laboratory, to achieve the stability of periodontal and dental tissues. Thus recovering the masticatory function and obtaining an acceptable aesthetic result to achieve the aesthetic and functional satisfaction that the patient sought. A 54-year-old female patient, systemically compromised, with previous pathologies, with the absence of teeth, long edentulous spaces, dental attrition, loss of vertical dimension and functional and aesthetic alterations. With a strict regime of established protocols, what was planned was fulfilled. The success of the treatment was based on: 1) maintaining the stability of dental periodontal and bone tissues. 2) recovery of masticatory function and return the vertical dimension; 3) obtaining an acceptable aesthetic result; 4) aesthetic and functional satisfaction of the patient.